Correction: Machine-learning-assisted screening of pure-silica zeolites for effective removal of linear siloxanes and derivatives. Issue 13 (23rd March 2020) - Lin, Shiru; Wang, Yekun; Zhao, Yinghe; Pericchi, Luis R.; Hernández-Maldonado, Arturo J.; Chen, Zhongfang
Abstract : Correction for 'Machine-learning-assisted screening of pure-silica zeolites for effective removal of linear siloxanes and derivatives' by Shiru Lin et al., J. Mater. Chem. A, 2020, 8, 3228–3237.